2014
DOI: 10.3390/s140305470
|View full text |Cite
|
Sign up to set email alerts
|

Gait Event Detection during Stair Walking Using a Rate Gyroscope

Abstract: Abstract:Gyroscopes have been proposed as sensors for ambulatory gait analysis and functional electrical stimulation systems. These applications often require detection of the initial contact (IC) of the foot with the floor and/or final contact or foot off (FO) from the floor during outdoor walking. Previous investigations have reported the use of a single gyroscope placed on the shank for detection of IC and FO on level ground and incline walking. This paper describes the evaluation of a gyroscope placed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…Additionally, Formento et al adopted a gyroscope based heuristic algorithm for gait event detection and reported that two TO gait events were missed in 20 TO events on up stairs terrain. Furthermore, three TO events were missed while one was wrongly detected in a total of 27 TO events on down stairs terrain [30]. With this data, the F1 score for their method was also computed and reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Formento et al adopted a gyroscope based heuristic algorithm for gait event detection and reported that two TO gait events were missed in 20 TO events on up stairs terrain. Furthermore, three TO events were missed while one was wrongly detected in a total of 27 TO events on down stairs terrain [30]. With this data, the F1 score for their method was also computed and reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, F1 scores of 0.96 and 0.76 for HS on up stairs and down stairs terrains were respectively obtained [2]. Formento et al proposed a rate gyroscope based heuristic algorithm for gait event detection, and recorded F1 scores of 0.95 and 0.93 for HS on up stairs and down stairs terrains respectively [30]. A major limitation of their study was that very few gait cycles were considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of studies have been devoted to the issue of determination of stress distributions in the femur equipped with various types of implants, and there are some papers in which loads affecting the hip joint in the conditions of movement were determined [1][2][3][4][5][6][7][8][9][10][11][12][13]. These loads were determined according to analytical and experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from fixed length segmentation, event-based segmentation techniques generally use a small fixed-length window to identify the events within one gait cycle (initial contact, flat foot or footoff) [16,17,18]. Chen et al extracted all peaks (mid-swing) from the signal and used the center of two consecutive peaks to identify the foot-flat segment [13].…”
Section: Introductionmentioning
confidence: 99%